Comparative Effectiveness of MRI, 4D-CT and Ultrasonography in Patients with Secondary Hyperparathyroidism - Mi J; Fang Y; Xian J; Wang G; Guo Y; Hong H; Chi M; Li YF; He P; Gao J; Liao W (Dove Medical Press, 2023)
Jiaoping Mi,1,2,* Yijie Fang,3,* Jianzhong Xian,4 Guojie Wang,3 Yuanqing Guo,5 Haiyu Hong,2 Mengshi Chi,2 Yong-Fang Li,2 Peng He,2 Jiebing Gao,3 Wei Liao2 1Department of Otolaryngology Head and Neck Surgery, The First Affiliated Hospital of Sun Yat-sen University, Zhuhai, Guangdong, People's Republic of China; 2Department of Otolaryngology Head and Neck Surgery, The Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai, Guangdong, People's Republic of China; 3Department of Radiology, The Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai, Guangdong, People's Republic of China; 4Department of Ultrasound, The Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai, Guangdong, People's Republic of China; 5Department of Spinal Surgery, The Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai, Guangdong, People's Republic of China*These authors contributed equally to this workCorrespondence: Wei Liao, Department of Otolaryngology Head and Neck Surgery, The Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai, Guangdong, 519020, People's Republic of China, Email liaowei23@mail.sysu.edu.cn Jiebing Gao, Department of Radiology, The Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai, Guangdong, People's Republic of China, Email Gaojb@mail.sysu.edu.cnObjective: Accurate preoperative localization of abnormal parathyroid glands is crucial for successful surgical management of secondary hyperparathyroidism (SHPT). This study was conducted to compare the effectiveness of preoperative MRI, 4D-CT, and ultrasonography (US) in localizing parathyroid lesions in patients with SHPT.Methods: We performed a retrospective review of prospectively collected data from a tertiary-care hospital and identified 52 patients who received preoperative MRI and/or 4D-CT and/or US and/or 99mTc-MIBI and subsequently underwent surgery for SHPT between May 2013 and March 2020. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of each imaging modality to accurately detect enlarged parathyroid glands were determined using histopathology as the criterion standard with confirmation using the postoperative biochemical response.Results: A total of 198 lesions were identified intraoperatively among the 52 patients included in this investigation. MRI outperformed 4D-CT and US in terms of sensitivity (P < 0.01), specificity (P = 0.455), PPV (P = 0.753), and NPV (P = 0.185). The sensitivity and specificity for MRI, 4D-CT, and US were 90.91%, 88.95%, and 66.23% and 58.33%, 63.64%, and 50.00%, respectively. The PPV of combined MRI and 4D-CT (96.52%) was the highest among the combined 2 modalities. The smallest diameter of the parathyroid gland precisely localized by MRI was 8× 3 mm, 5× 5 mm by 4D-CT, and 5× 3 mm by US.Conclusion: MRI has superior diagnostic performance compared with other modalities as a first-line imaging study for patients undergoing renal hyperparathyroidism, especially for ectopic or small parathyroid lesions. We suggest performing US first for diagnosis and then MRI to make a precise localization, and MRI proved to be very helpful in achieving a high success rate in the surgical treatment of renal hyperparathyroidism in our own experience.Keywords: MRI, 4D-CT, ultrasonography, SHPT, preoperative localization, parathyroidectomy